PERANCANGAN MULTIMEDIA SEBAGAI ALAT BANTU PROSEDUR STUFFING DENGAN METODE DEMONSTRASI UNTUK SUPIR EKSPOR DI PT. ASIA PACIFIC FIBERS TBK KALIWUNGU KENDAL - Nofa Trifanto (Pixel :Jurnal Ilmiah Komputer Grafis, 2019)
This research is motivated by the problem of lack of understanding and attention export drivers in carrying out work in the factory area because of the facilities used still using conventional methods, so that export drivers experience difficulty in understanding work processes in terms of stuffing and resulting procedures losses in terms of time, energy and financial. The way to overcome this in this study is the use of use outreach media as a tool for export officers who display 2D images and interesting explanations as well as music, using the Demonstration delivery method so that export drivers get better performance and easily understand the material delivered by the export officer. This research uses the Research and Development product development method (RnD), using 6 out of 10 stages of research namely potential and problems, gathering data, product design, design validation, design improvements and product trials. The results of this study are to produce aids for export officers by using Adobe Flash CS3 software with validity values ​​from media experts 3.0 where it is declared feasible, the validity value of the material expert is 3.3 where stated very feasible, and increase the understanding of export drivers from 65% to start upto 87.50%